A NETWORK PHARMACOLOGY-BASED DRUG REPURPOSING STUDY OF LEVETIRACETAM UNCOVERS ITS INTERACTION WITH MULTI-DRUG TARGETS IN PARKINSON'S DISEASE - PANDEY, NEERAJ; KARTHIK, V. P.; SELVA, PREETHA; HAZEENA, PHILO (International Journal of Applied Pharmaceutics, 2024)
Objective: The current study utilized network pharmacology to examine how Levetiracetam interacts with specific drug targets associated with Parkinson's Disease (PD) treatment. Methods: We used information from Kyoto Encyclopedia of Genes and Genome (KEGG) studies and Protein-Protein Interaction (PPI) pathway analysis to create a network that depicts the relationships between Levetiracetam and PD targets. Further investigation involved PPI analysis, molecular docking, and Molecular Dynamics (MD) simulation studies, ultimately pinpointing five protein targets. Their participation in pathways such as Ribonucleic acid Polymerase II-specific Deoxyribonucleic acid binding Transcription Factor Binding (Gene Ontology [GO]:0061629), Axon (GO: 0030424), and Excitatory Postsynaptic Potential was emphasized by GO and KEGG pathway enrichment. Additionally, Dopamine Receptor D2 (DRD2), Solute Carrier Family 6 Member 3 (SLC6A3), Glycogen Synthase Kinase 3 Beta (GSK3B), Poly (ADP-ribose) Polymerase 1 (PARP1) and Myeloperoxidase (MPO) were identified as protein targets through PPI and molecular docking analysis. Results: The results of molecular docking showed that protein targets, SLC6A3, have highest binding affinity with Levetiracetam. The MD Simulation result of Levetiracetam-SLC6A3 docked complex represented the complex to be quite stable with few conformational changes in the SLC6A3 structure. DRD2, SLC6A3, GSK3B, PARP1, MPO were recognized as the likely protein targets of Levetiracetam for treating PD. SLC6A3 was considered as a target of Levetiracetam in PD. Conclusion: Our study revealed the mechanism of Levetiracetam in the treatment of PD and can contribute to more effective treatment for the same. By identifying key protein targets, this research lays the groundwork for future studies that could further explore Levetiracetam’s efficacy.